Subarachnoid and intracerebral hemorrhage in cocaine abusers - Aleksić Ivan; Džambas Jelena; Marinković Nadica; Šegrt Zoran; Nikolić Marina (Vojnosanitetski Pregled)
Background/Aim. Cocaine is an alkaloid extracted from the leaves of the plants Erythroxylum coca and Erythroxylum novogranatense. It can be taken orally, intranasally, intravenously, by inhalation, or intragenitally. Cocaine abuse can cause subarachnoid and intracerebral hemorrhage. The aim of this study was to determine cocaine and benzoylecgonine (BZ) concentrations in various body fluids and organs, the frequency of subarachnoid and intracerebral hemorrhage, and the relationship of concentration of cocaine and BZ in different body fluids with subarachnoid and intracerebral hemorrhage. Methods. The study analyzed a total of 26 autopsies reports from 2005 to 2018 with detected cocaine and/or BZ in the bodies during a forensic autopsy at the Institute of Pathology and Forensic Medicine, Military Medical Academy in Belgrade, Serbia. Brain tissue was taken for histopathological analysis and blood from the femoral vein, while urine, gastric content, brain, kidney, and liver with gallbladder samples were taken for toxicological analyses. Results. There were 26 autopsied patients aged 23 to 56 years (mean age 33.77±8.52); 20 (75.92%) were men and 6 (23.08%) were women. Cocaine was found in the blood of 12 (46.15%), in the urine of 15 (57.69%), and in the brain of 8 (30.77%) autopsied patients. BZ was found in the blood of 20 (76.92%), in the urine of 21 (80.77%), and in the brain of 10 (38.46%) autopsied patients. Subarachnoid hemorrhage was found in 10 (38.46%), intracerebral hemorrhage in 18 (69.23%), and both subarachnoid and intracerebral hemorrhage in 6 (23.07%) autopsied patients. Intracerebral (focal and perivascular) hemorrhage was more frequent. There were statistically significantly higher concentrations of both cocaine and BZ in most of the body fluids and organs of examinees with intracranial hemorrhage compared to examinees without hemorrhage. Conclusion. Subarachnoid and intracerebral hemorrhage were frequent findings in autopsied cocaine abusers. The correlation between subarachnoid and intracerebral hemorrhage and cocaine concentrations in blood was moderate. There were strong correlation between subarachnoid and intracerebral hemorrhage and BZ concentrations in almost all the samples.